Enhanced Recovery of Apple Pomace Phenolic Compounds: Optimizing Subcritical Water Extraction - Mahsa Derakhshan; Amir Hossein Elhami Rad; Majid Javanmard Dakheli; Parvin Sharayei; Mohammad Armin (International Journal of Food Science)
This study was aimed at optimizing the extraction process of phenolic compounds, particularly antioxidants and antimicrobial agents, from apple pomace using the subcritical water extraction method. The Box–Behnken experimental design was utilized to ascertain the optimal extraction conditions, focusing on maximizing yield, phenolic compound content, and antioxidant activity. Three independent variables were investigated: extraction temperature (120°C, 140°C, and 160°C), extraction time (20, 30, and 40 min), and water-to-apple pomace ratio (1:20, 1:40, and 1:60 g/mL). The optimized subcritical water extraction process yielded a significantly higher extraction efficiency (18.05%), total phenolic content (1341.11 mg/100 g), and 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging capacity (92.39%) compared to the conventional maceration method. The experimental results aligned well with the predicted values obtained from the Box–Behnken model. The antimicrobial properties of the optimized extract were assessed against Staphylococcus aureus, Escherichia coli, and Aspergillus niger through the serial dilution method. The extract at a concentration of 30 mg/100 mL exhibited superior antifungal and antibacterial properties compared to potassium sorbate (10 mg/100 mL). This research demonstrates the potential of subcritical water extraction as a sustainable and efficient method for extracting phenolic compounds from apple pomace, offering a promising alternative to conventional methods and contributing to the valorization of agricultural waste.